Recommendations on pregnancy, childbirth and aftercare in epidermolysis bullosa: a consensus‐based guideline. (1st April 2022) - Greenblatt, D.T.; Pillay, E.; Snelson, K.; Saad, R.; Torres Pradilla, M.; Widhiati, S.; Diem, A.; Knight, C.; Thompson, K.; Azzopardi, N.; Werkentoft, M.; Moore, Z.; et al.
Abstract: Linked Comment:  A.W. Lucky and E. Pope. Br J Dermatol 2022; 186 :602–603. Plain language summary available online